Induced Innovation and Energy Prices - Popp, David (American Economic Review, 2002)
I use U.S. patent data from 1970 to 1994 to estimate the effect of energy prices on energy-efficient innovations. Using patent citations to construct a measure of the usefulness of the existing base of scientific knowledge, I consider the effect of both demand-side factors, which spur innovative activity by increasing the value of new innovations, and supply-side factors, such as scientific advancements that make new innovations possible. I find that both energy prices and the quality of existing knowledge have strongly significant positive effects on innovation. Furthermore, I show that omitting the quality of knowledge adversely affects the estimation results.